Effects of Remittance on Financial Savings in Nepal: An Exploration through Auto-Regressive Distributed Lag Approach - Lamsal, Mani Ratna; Soneja, Sakshi (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Foreign remittances have emerged as a significant source of external finance for many developing countries, and Nepal is no exception. The family members and the government of the country of origin derive the maximum possible advantages of remittances in various fields, and it is becoming a more stable source of external finance. It is used in multiple sectors, including financial savings in Nepal. Despite the increasing importance of remittances in the Nepalese economy, the relationship between remittances and financial savings has not been adequately studied yet. Hence, the prime objective of this paper is to analyse the effects of remittances on the financial savings in Nepal. The Auto-Regressive Distributed Lag (ARDL) Bounds Testing Model is employed in this study to identify the effects of remittances on financial savings in Nepal. The time series data for 24 years, spanning 2001-2024, are collected from various published sources of the Nepal government, such as the Ministry of Finance (MOF), Nepal Rastra Bank (NRB) and National Statistics Office (NSO). This study has identified a positive and significant relationship between remittances and financial savings in Nepal. The impacts of other control variables, NBF, are negative and significant. The Nepal government and other concerned agencies should encourage migrants to send remittances only from formal banking channels, encouraging them to save, which helps capital formation, investment and job creation in Nepal. It also solves the liquidity crisis and foreign exchange constraints in the nation.